A journey through the emergence of nanomedicines with poly(alkylcyanoacrylate) based nanoparticles. (3rd July 2019) - Vauthier, Christine
Abstract: Starting in the late 1970s, the pioneering work of Patrick Couvreur gave birth to the first biodegradable nanoparticles composed of a biodegradable synthetic polymer. These nanoparticles, made of poly(alkylcyanoacrylate) (PACA), were the first synthetic polymer-based nanoparticulate drug carriers undergoing a phase III clinical trial so far. Analyzing the journey from the birth of PACA nanoparticles to their clinical evaluation, this paper highlights their remarkable adaptability to bypass various drug delivery challenges found on the way. At present, PACA nanoparticles include a wide range of nanoparticles that can associate drugs of different chemical nature and can be administered in vivo by different routes. The most recent technologies giving the nanoparticles customised functions could also be implemented on this family of nanoparticles. Through different examples, this paper discusses the seminal role of the PACA nanoparticles' family in the development of nanomedicines.